The impact of humanization on the sustainability of Malaysian SMEs - Anas, Abu Jaish; Murdipi, Rafiqa; Abdul Razak, Dzuljastri; Mohd Alwi, Norhayati (Human Resource Management Academic Research Society, 2024)
Small and medium-sized enterprises are recognized as critical drivers of economic growth in various developing countries. Despite their achievements, SMEs in different sectors continue to face multiple challenges and issues. The COVID-19 pandemic is one of the most recent issues affecting SMEs' business operations, including Malaysia. Malaysian SMEs faced difficulties due to the implementation of the MCO, leading to limited supplies, a significant sales decline, reduced cash flows, and restrictions on in-person transactions. Many Malaysian SMEs have shut down and been unable to survive during this crucial period. This phenomenon has caused worry about the sustainability of SMEs. To achieve sustainability, businesses, especially SMEs, need higher profitability and faster response to market changes. The sustainability of SMEs could be achieved through increased sufficiency and flexibility of their resources. Many SMEs have embraced the resources in an uncertain environment to address sustainability concerns. Improving the resources among the SMEs has proven valuable in supporting SMEs' competitiveness. Many faced failures in successfully achieving the sufficiency of the resources due to various challenges. The challenge of providing SMEs with efficient and flexible resources arises from the need for large capital, lack of specific resources, knowledge gaps, insufficient funds, lack of human resources, lack of support system, inadequate planning, and humanization limitations. This paper deliberates on the importance of having dynamic resource capabilities to ensure SMEs' successful adaptation of proper support systems, value-added services, CSR, VBI, SDGS and Humanization. The discussion focuses on the importance of dynamic capabilities to address uncertain issues, which ultimately determines their sustainability.